"Мама, почему у меня синдром Дауна?" - Филпс Каролина (Серия "Любовь изгоняет страх", 2012)
Экземпляры: Аб (20121119) / Инвентарный номер: 99133 / Цена: 191.18 / Сис.шифр: 74.3 / Авт.знак: Ф 56 / ББК: 74.3